Shoulder Arms! Images of War in American Silent Cinema (KULT_online, 2011)
Annika Requardt's dissertation analyses strategies of visualization and narrativization in American war films of the silent era, employing theories of collective memory and visual culture. It covers a wide range of fictional and non-fictional films that depict the Spanish-American War, World War I, and the Civil War. Requardt shows how, by concretion and repetition, there emerges a standardized and schematic tradition of filmic images that provides war with meaning, and offers a way for the nation to identify itself. However, lacking empirical evidence, the author deduces the remembrance of war simply from the existence of films and their images without taking the particular reception into account. While she therefore cannot utilize the full potential of the memory culture approach, the analyses of the films are very convincing in their own right.